Direct seed marketing program in Ethiopia in 2013: An operational evaluation to guide seed-sector reform - Benson, Todd; Spielman, David J.; Kasa, Leulsegged (International Food Policy Research Institute, 2014)
In 2013 the Bureaus of Agriculture in the regional states of Amhara, Oromia, and Southern Nations, Nationalities, and Peoples of Ethiopia supported a program of direct marketing of certified seed by seed producers to farmers across 31 woredas (districts). This program stands in contrast to the dominant procedure for supplying such seed in which farmers register with local agricultural offices or extension agents to purchase seed for the coming cropping season and then receive seed either directly from these local offices or through local cooperatives. The evaluation shows that competition between entrepreneurial seed producers to capture a substantial portion of the market of farmer-customers for their seed to enable their firms to remain in business will propel wider and more effective distribution of new and improved hybrid maize to more and more farmers.